The genetics of Canadian type 3 von Willebrand disease: further evidence for co‐dominant inheritance of mutant alleles. Issue 3 (13th March 2013) - Bowman, M.; Tuttle, A.; Notley, C.; Brown, C.; Tinlin, S.; Deforest, M.; Leggo, J.; Blanchette, V.S.; Lillicrap, D.; James, P.; ,
Summary Background Type 3 von Willebrand disease (VWD) is the most severe form of the disease and is classically inherited in an autosomal recessive fashion. Objectives The aim of the current study was to investigate the molecular pathogenesis of a Canadian cohort of type 3 VWD patients. Patients and methods Thirty‐four families comprised of 100 individuals were investigated. Phenotypic data, including bleeding scores (BS), von Willebrand factor (VWF) laboratory values and anti‐VWF inhibitor status were included as well as sequence analysis. Results We identified 31 different mutations (20 novel): 8 frameshift, 5 splice site, 9 nonsense, 1 gene conversion, 6 missense and 2 partial gene deletion mutations. The majority of mutations identified were in the propeptide (42%); index cases (IC) with these mutations exhibited more severe bleeding (BS = 22) than those with mutations elsewhere in VWF (BS = 13). Sixty‐two out of 68 (91%) mutant alleles were identified. Twenty‐nine IC (85%) had a VWF null genotype identified; 17 homozygous, 12 compound heterozygous. In five IC (15%), two mutant VWF alleles were not identified to explain the type 3 VWD phenotype. In four ICs only one mutant VWF allele was identified and in one IC no mutant VWF alleles were identified. Conclusions We have investigated the molecular pathogenesis of a Canadian cohort of type 3 VWD patients. Obligate carriers are not phenotypically silent in the Canadian population; 48% have been diagnosed with type 1 VWD. In approximately 50% of families in this study the inheritance pattern for type 3 VWD is co‐dominant and not recessive.